Sex differences in independence in activities of daily living early in stroke rehabilitation - Liljehult, Monique Mesot; Euler‐Chelpin, My Catarina; Christensen, Thomas; Buus, Lise; Stokholm, Jannik; Rosthøj, Susanne (Brain and behavior, 2021)
Background Current stroke research suggests that there are differences between females and males regarding incidence, stroke risk factors, stroke severity, outcome, and mortality. The few studies that have investigated sex differences in rehabilitation 8–12 months poststroke found that males are more independent, compared to females. Objectives To investigate if there is a difference in the improvement of independence in activities of daily living (ADL) between females and males in the acute phase (first 2 weeks) of stroke rehabilitation in a Danish population. Methods A prospective cohort study enrolling patients admitted to the hospital's rehabilitation ward with a stroke diagnosis from January 1, 2016, to March 17, 2017. Baseline and follow‐up data regarding the primary outcome, Barthel‐100 index, were analyzed using an adjusted linear mixed model. Results The study included 206 patients (83 females). Females were older at admission and more males lived with a partner. No differences in stroke severity or any of the risk factors were found. There were no differences between female and male scores at baseline. In the adjusted linear mixed model, quantifying the difference between follow‐up and baseline Barthel‐100 score, females increased their Barthel‐100 score by 20.8 points (95% confidence interval (CI) 15.4–26.3) and males with 29.0 points (95% CI 24.6–33.4). Conclusion In a homogeneous sample of stroke survivors undergoing specialized 24‐h stroke rehabilitation for 11–14 days, females were more dependent in ADL than males. Females are more dependent than males in activities of daily living after stroke rehabilitation